Grounding Basic Equality - Orr, James (De Ethica, 2023)
Although egalitarianism has been the dominant orthodoxy in Anglophone social and political philosophy for many decades, there have been surprisingly few attempts to account for the axiom on which it rests, namely that human moral worth does not come in degrees. This article begins by rehearsing and evaluating two families of approaches to the grounding problem. The first favours accounts that seek to preserve consistency with metaphysical naturalism, while the second relies on more philosophically contentious claims about the metaphysical status of the human person. I then outline reasons for supposing that none of these accounts of basic equality offers a convincing theoretical foundation for egalitarianism. I conclude by sketching permutations of a theological account before arguing that one of these variations satisfies many of the explanatory criteria that a successful solution requires.